Landscape mosaic in the treeline ecotone on Mt Rodjanoaivi, Subarctic Finland - Gabriele Broll; Friedrich-Karl Holtmeier; Kerstin Anschlag; Hans-Jörg Brauckmann; Sabine Wald; Birgit Drees (Geographical Society of Finland, 2007)
The objective of this paper is to differentiate the landscape in the treeline ecotone in Subarctic Finland with an examination of its mosaic structure and functional role in treeline dynamics. Highly varying topography is a key factor controlling drainage conditions, vegetation, local climates and soils. Natural drainage classes, soil data (pH, Corg, Nt, C/N ratio, moisture) and dominant vegetation were used to characterize site conditions and to show the grouping of six representative sites along a synthetic topographical transect (model). The abrupt increase in soil moisture and pH values at the distal end of the lowest zones indicates a relatively sharp and ecologically important limit between well drained sites (ridge tops, upper valley side, interfluves) and valleys with both poorly and very poorly drained sites. Remains of birch wood in wind-scarps, hummocks and peaty layers give evidence of former open birch forest in present treeless sites. Forest decline has enforced the contrasts in site conditions between windswept and snow accumulating topography. The landscape mosaic and resultant site conditions are strongly influencing treeline dynamics and consequently, the landscape mosaic needs to be carefully considered when discussing the possible effects of the changing climate in the treeline ecotone.